Comparison of quasi‐spherical surfaces – application to corneal biometry. Issue 3 (1st September 2016) - Polette, Arnaud; Mari, Jean‐Luc; Brunette, Isabelle; Meunier, Jean
Abstract : In this study, the authors present two new techniques with their own particular advantages dedicated to the authentication of a person based on the three‐dimensional geometry of the cornea. A device known as corneal topographer is used for capturing the shape of each cornea. Until now only a few studies on corneal biometry have been conducted and they were limited only to the anterior surface. In this study, since the whole cornea is a tissue layered by two (anterior and posterior) surfaces, the authors propose to use both surfaces to characterise the corneal shape. The first proposed method consists of comparing coefficients from a spherical harmonics decomposition, and this allows to do a fast comparison that can be used to perform many‐to‐one comparisons. The second approach is based on the minimal residual volume between two corneas after a registration step, this geometry‐based method is more accurate but slower, and is thus used to perform one‐to‐one comparisons. A cascade fusion scheme is also proposed to benefit from the advantages of both methods. The authors' study demonstrates that corneal shape could be used for biometry. The two proposed methods have been tested and validated on a dataset of 257 corneas.